Effect of supplementing Medicago sativa (alfalfa) on some parameters of bovine milk - Cruz Carrillo, Anastasia (2017)
The aim of this study was to determine whether alfalfa supplementation in milking cows could generate an antioxidant effect and modify the composition of milk fatty acids. Nineteen cows were distributed in a treated group (supplemented with alfalfa; n=11) and a control group (n=8). The level of oxidation of milk fat (copper soap test), compositional quality and the presence of fatty acids (gas chromatography) in milk were determined. The milk fat of supplemented animals showed greater stability and less oxidation compared to the control group, showing an antioxidant effect even in milk kept during 14 days at room temperature. There was an increase of polyunsaturated fatty acids and a decrease of the saturated ones, and the percentage of total milk fat increased. It is concluded that alfalfa supplementation gives greater stability to milk fat due to its antioxidant effect, without affecting the reproductive performance of cows and improves the proportion of polyunsaturated fatty acids with a decrease of saturated ones, which would be more beneficial to consumer health.